2023
DOI: 10.1038/s41392-023-01415-6
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxybutyrate ameliorates insulin resistance by inhibiting PPARγ Ser273 phosphorylation in type 2 diabetic mice

Abstract: Abstract3-Hydroxybutyrate (3HB) is a small ketone body molecule produced endogenously by the body in the liver. Previous studies have shown that 3HB can reduce blood glucose level in type 2 diabetic (T2D) patients. However, there is no systematic study and clear mechanism to evaluate and explain the hypoglycemic effect of 3HB. Here we demonstrate that 3HB reduces fasting blood glucose level, improves glucose tolerance, and ameliorates insulin resistance in type 2 diabetic mice through hydroxycarboxylic acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Previously, we found that 3HB had a protective effect on the liver of mice with type 2 diabetes[16]. CCl 4 directly causes liver cell injury, necrosis and inflammation, and is widely used in the establishment of animal models of liver fibrosis and cirrhosis[18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we found that 3HB had a protective effect on the liver of mice with type 2 diabetes[16]. CCl 4 directly causes liver cell injury, necrosis and inflammation, and is widely used in the establishment of animal models of liver fibrosis and cirrhosis[18].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that 3HB had a protective effect on the liver of mice with type 2 diabetes [16].…”
Section: Different Doses Of 3hb All Exhibit Attenuation Of CCL 4 -Ind...mentioning
confidence: 88%
See 2 more Smart Citations
“…Further studies are needed to gain a deeper understanding of these differences. 3-Hydroxybutyrate, originating from the increased β-oxidation of free fatty acids [ 40 ], is found in higher concentrations in the plasma of T2DM patients [ 41 ] and has been shown to ameliorate insulin resistance in T2DM mice through the HCAR2/Ca 2+ /cAMP/PKA/Raf1/ERK1/2/PPARγ pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 99%